PENYALAHGUNAAN KEADAAN DALAM PERJANJIAN JUAL BELI DENGAN HAK MEMBELI KEMBALI (Analisis Putusan Mahkamah Agung Nomor 3191 K/Pdt/2016) - Wardah Wardah (Universitas Tidar, 2018)
Adat Law knows no sale and purchase of land with rights or promises to buy back. The existence of this provision overrides the terms of sale and purchase which are regulated in the Civil Code that allow the sale and purchase with the right to buy back. Although the sale and purchase of land with the right to buy back has been declared prohibited in the National Land Law, in practice there are still many such conditions resulting in land disputes as occurred in the Decision of the Supreme Court of the Republic of Indonesia Number 3191 K / Pdt / 2016. The author in this study wants to examine and analyze further the Decidendi Ratio of the Decision of the Supreme Court of the Republic of Indonesia Number 3191 K / Pdt / 2016 and the validity of the Deed of Sale and Purchase Agreement which contains the right to repurchase. The research method used is normative legal research, namely legal research carried out by examining library materials or secondary legal materials while the problem approach is carried out using a legal approach and conceptual approach. The results showed that the enactment of the Agrarian Basic Law which made Adat Law as a National Land Law removed the existence of buying and selling institutions with the right to repurchase. Legal actions carried out by the parties in the form of an Agreement to Bind Sale and Purchase and a Proxy of Selling accompanied by a clause on the right to buy back are null and void. The Notary Deed containing the Agreement on the Binding of Sale and Purchase and Selling Authorization accompanied by the right clause to repurchase is still valid and binding on the parties until the Deed is canceled based on the Court Decision